Making Uzbekistan : Nation, Empire, and Revolution in the Early USSR - Khalid, Adeeb, 1964- (Book collections on Project MUSE., 2015)
This book chronicles the tumultuous history of Central Asia in the age of the Russian revolution. Traumatic upheavals - war, economic collapse, famine - transformed local society and brought new groups to positions of power and authority in Central Asia, just as the new revolutionary state began to create new institutions that redefined the nature of power in the region. This was also a time of hope and ambition in which local actors seized upon the opportunity presented by the revolution to reshape their society.